2019
DOI: 10.1002/aelm.201900570
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relationship Between Grain Size and Electrical Properties in (K,Na)NbO3‐Based Lead‐Free Piezoelectric Ceramics

Abstract: The 0.5 wt% MnO2‐doped 0.95(K0.5Na0.5)(Nb0.965Sb0.035)O3‐0.01CaZrO3‐0.04(Bi0.5K0.5)(Hf0.98Ti0.02)O3 (95KNNS‐1CZ‐4BKHT) lead‐free ceramics with grain size from 0.31 to 3.83 µm are fabricated by hot‐press sintering (HPS), microwave sintering (MS), conventional sintering (CS), two‐step sintering (TSS), and a combination of two of the above‐mentioned methods. Then, the grain size effects on the phase transition, electrical properties, domain structure, and temperature stability of the ceramics are investigated. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…Generally, the composition-dependent phase structure can also be identified by εr-T curves [32]. With an increasing x, TO-T gradually increases from 44 oC (at x=0) to 118 oC (at x=0.03) and TR-O slightly increases from -50 oC to -36 oC (Figures 4(a-e)).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Generally, the composition-dependent phase structure can also be identified by εr-T curves [32]. With an increasing x, TO-T gradually increases from 44 oC (at x=0) to 118 oC (at x=0.03) and TR-O slightly increases from -50 oC to -36 oC (Figures 4(a-e)).…”
Section: Resultsmentioning
confidence: 95%
“…despite the reduced AGS and the reduced degree of phase coexistence. It was reported that the piezoelectricity was enhanced by the increasing grain size and the construction of multi-phase 14 coexistence [32,39]. As compared in Table 2, the ceramics with x=0.03 show the superior electrical properties to those of other KNN-based ceramics with an AGS of 1-2 µm [32,[40][41][42][43].…”
Section: Resultsmentioning
confidence: 99%
“…Due to Pb toxicity in commercial lead‐based piezo‐materials, lead‐free piezoelectrics have received much attention in recent years . Potassium‐sodium niobate [(K, Na)NbO 3 , KNN] is one of the most promising lead‐free candidates because of its high Curie temperature ( T C =415 °C) and relatively good piezoelectric constant ( d 33 ) . For small signal applications, such as sensors and microphones, d 33 is a research emphasis.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Potassium-sodium niobate [(K, Na)NbO 3 , KNN] is one of the most promising lead-free candidates because of its high Curie temperature (T C =415 °C) and relatively good piezoelectric constant (d 33 ). 8,[25][26][27][28] For small signal applications, such as sensors and microphones, d 33 is a research emphasis. d 33 in KNN-based materials has been promoted greatly, which is even comparable to that obtained in lead-based materials, via technology improvement (reactive templated grain growth) and the establishment of phase boundaries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation